Using FLIM-FRET to Measure Conformational Changes of Transglutaminase Type 2 in Live Cells - Caron, Nicholas S.; Munsie, Lise N.; Keillor, Jeffrey W.; Truant, Ray (PLOS ONE, 2012)
Transglutaminase type 2 (TG2) is a ubiquitously expressed member of the transglutaminase family, capable of mediating a transamidation reaction between a variety of protein substrates. TG2 also has a unique role as a G-protein with GTPase activity. In response to GDP/GTP binding and increases in intracellular calcium levels, TG2 can undergo a large conformational change that reciprocally modulates the enzymatic activities of TG2. We have generated a TG2 biosensor that allows for quantitative assessment of TG2 conformational changes in live cells using Förster resonance energy transfer (FRET), as measured by fluorescence lifetime imaging microscopy (FLIM). Quantifying FRET efficiency with this biosensor provides a robust assay to quickly measure the effects of cell stress, changes in calcium levels, point mutations and chemical inhibitors on the conformation and localization of TG2 in living cells. The TG2 FRET biosensor was validated using established TG2 conformational point mutants, as well as cell stress events known to elevate intracellular calcium levels. We demonstrate in live cells that inhibitors of TG2 transamidation activity can differentially influence the conformation of the enzyme. The irreversible inhibitor of TG2, NC9, forces the enzyme into an open conformation, whereas the reversible inhibitor CP4d traps TG2 in the closed conformation. Thus, this biosensor provides new mechanistic insights into the action of two TG2 inhibitors and defines two new classes based on ability to alter TG2 conformation in addition to inhibiting transamidation activity. Future applications of this biosensor could be to discover small molecules that specifically alter TG2 conformation to affect GDP/GTP or calcium binding.